2007
DOI: 10.1161/circulationaha.107.725101
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Public Knowledge of Peripheral Arterial Disease

Abstract: Background-Lower-extremity peripheral arterial disease (PAD) is associated with decreased functional status, diminished quality of life, amputation, myocardial infarction, stroke, and death. Nevertheless, public knowledge of PAD as a morbid and mortal disease has not been previously assessed. Methods and Results-We performed a cross-sectional, population-based telephone survey of a nationally representative sample of 2501 adults Ն50 years of age, with oversampling of blacks and Hispanics. The survey instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(101 citation statements)
references
References 39 publications
4
93
0
Order By: Relevance
“…Third, financial factors can influence a patient's utilization of healthcare, particularly if they choose not to pursue the workup of a condition which is frequently only mildly distressing. 10,33 Last, a patient's mental status can impair a timely diagnosis. Psychologically, a person who is depressed may have functional impairment and be noncompliant, 34 while physiologically, depression may exacerbate endothelial dysfunction, circulating catecholamine levels, and platelet reactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, financial factors can influence a patient's utilization of healthcare, particularly if they choose not to pursue the workup of a condition which is frequently only mildly distressing. 10,33 Last, a patient's mental status can impair a timely diagnosis. Psychologically, a person who is depressed may have functional impairment and be noncompliant, 34 while physiologically, depression may exacerbate endothelial dysfunction, circulating catecholamine levels, and platelet reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, surveys have shown that physicians feel unfamiliar with PAD demographics, screening and diagnostic approaches. 10,11 Given that secondary prevention measures have been shown to improve outcomes in PAD, 12 cases where the diagnosis of PAD is missed may result in preventable morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Indeed, history and physical examination have significant limitations in identifying those individuals with PAD, as the majority have atypical symptoms or are considered asymptomatic. 4 This has significant public health implications since PAD is considered a coronary artery disease risk equivalent, and, if unrecognized, carries significant morbidity and mortality. 5 Even those patients with asymptomatic PAD tend to have shorter 6-minute walk test results and poorer functional status.…”
Section: Asymptomatic Padmentioning
confidence: 99%
“…Importantly, most of these patients are over the age of 65 years. [2,3] Indeed, history and physical examination have significant limitations in identifying those individuals with PAD, as the majority have atypical symptoms or are considered asymptomatic [4]. This has significant public health implications since PAD is considered a coronary artery disease risk equivalent, and, if unrecognized, carries significant morbidity and mortality [5].…”
Section: Asymptomatic Padmentioning
confidence: 99%